A review of COVID-19-related thrombosis and anticoagulation strategies specific to the Asian population - Kai Chin Poh; Victoria Yu Jia Tay; Sarah Huixin Lin; Huei Leng Chee; Suhitharan Thangavelautham (Singapore Medical Journal)
The coronavirus disease 2019 (COVID-19) pandemic has placed an immense burden on healthcare systems worldwide. There is intensive research targeted at better understanding of the virus pathogenicity, development of effective treatment strategies and vaccines against COVID-19. It is increasingly being recognised that the pathogenicity of COVID-19 extends beyond the respiratory system. In severe cases, there can be widespread activation of the immune system, vascular injury and a resultant pro-thrombotic state. Severe COVID-19 is widely regarded as a risk factor for venous thromboembolism. Interim European and American guidelines have been created to guide anticoagulation strategies in COVID-19 patients. However, it is unclear if these guidelines can be extrapolated directly to Asians, in whom there are differences in the baseline risk of thrombosis and bleeding. Our review article aimed to summarise the current understanding of arteriovenous thromboembolic complications in COVID-19 and discuss management strategies for prevention and treatment of thrombotic events in Asian COVID-19 patients.